The effect of entrepreneurial knowledge, entrepreneurial motivation and entrepreneurial self-efficacy on entrepreneurial intention among students - Fiqriyani, Auliya; Prayekti, Prayekti; Lysander, Mohammad Ahyar Syafwan (LPMP Imperium, 2025)
This study aims to determine the effect of entrepreneurial knowledge, entrepreneurial motivation, and entrepreneurial self-efficacy on entrepreneurial intention in Management Study Program students of the Faculty of Economics in 2021, Sarjanawiyata Tamansiswa University. The method used in this research is quantitative research, using a survey method involving 72 respondents through the distribution of questionnaires. The results of this study indicate that entrepreneurial knowledge, entrepreneurial motivation, and entrepreneurial self-efficacy have a positive and simultaneous effect on entrepreneurial intentions. Public interest statements This research has significant relevance for students, as it highlights the influence of knowledge about entrepreneurship, entrepreneurial spirit, and confidence in starting a business, which collectively can increase entrepreneurial intention.